Silent practices becoming norms: planned napping for nurses during intensive care night shifts – a focus group study - Löfqvist, Carita; Siivonen, Johanna Kaarina; Axelin, Anna; Peltonen, Laura-Maria; Ritmala, Marita (SAGE Publications, 2026)
Background:
Night shifts in intensive care units (ICUs) are associated with significant physical and cognitive fatigue among nurses, which may affect staff well-being and patient safety. Although short naps have been shown to reduce fatigue, their implementation in ICUs remains limited and poorly understood.
Aim:
This study explored ICU nurses’ and nurse managers’ perceptions of planned napping.
Methods:
A qualitative descriptive design was used, involving nine focus group interviews (n = 20) across three Finnish ICUs. Data were analysed using inductive content analysis.
Results:
Participants described severe fatigue during night shifts and acknowledged the benefits of planned napping, including improved alertness, reduced errors, and enhanced well-being. Informal napping was common, but formal structures were lacking. Barriers included unclear policies, cultural resistance, and logistical challenges; whereas facilitators involved organisational culture, environment, scheduling, and managerial support. Emphasis was placed on fairness, flexibility, and clear protocols.
Conclusions:
Planned napping was perceived as a valuable strategy for managing fatigue, but successful implementation requires institutional support and context-sensitive planning. This study provides practical insights into implementing planned napping in high-acuity environments and supports the development of structured, evidence-informed protocols to promote staff well-being, patient safety and sustainable nursing practices.